2008
DOI: 10.1007/s12517-008-0014-0
|View full text |Cite
|
Sign up to set email alerts
|

زلزالية شبه جزيرة سيناء - مصر

Abstract: The

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(5 citation statements)
references
References 42 publications
0
5
0
Order By: Relevance
“…The high seismic activity of the AQ zone is attributed to the Gulf of Aqaba's left-lateral strikeslip movement (Ben-Avraham 1985;Toni 2012;Toni et al, 2016Toni et al, , 2019aBadreldin et al 2019;Hagag et al 2019). Abdel-Rahman et al (2009) reported that recent earthquakes all over the Sinai Peninsula are larger than historical ones, which agrees with the region's neotectonic reactivation models. The vertical distribution of the earthquake focal depths (Fig.…”
Section: Resultsmentioning
confidence: 56%
See 1 more Smart Citation
“…The high seismic activity of the AQ zone is attributed to the Gulf of Aqaba's left-lateral strikeslip movement (Ben-Avraham 1985;Toni 2012;Toni et al, 2016Toni et al, , 2019aBadreldin et al 2019;Hagag et al 2019). Abdel-Rahman et al (2009) reported that recent earthquakes all over the Sinai Peninsula are larger than historical ones, which agrees with the region's neotectonic reactivation models. The vertical distribution of the earthquake focal depths (Fig.…”
Section: Resultsmentioning
confidence: 56%
“…4) depicts the tectonic action in the Sinai Peninsula, with a high concentration in its southern portion parallel to the Gulf of Suez and the Gulf of Aqaba motions. According to the description of seismic source zones of Abdel-Rahman et al (2009), the most active zones are the Aqaba (AQ) and the southern Gulf of Suez (SGZ). The crustal motions between the Arabian plate, African plate, and Sinai subplate result in a high seismicity rate in the SGZ zone.…”
Section: Resultsmentioning
confidence: 99%
“…These include Fairhead (1968); Sykes (1970); Fairhead andGirdler (1970, 1972); Poirier and Taher (1980); Ambraseys and Melville (1983);El-Isa et al (1984); Alsinawi (1986); El-Isa and Al- Shanti (1989); Pedone et al (1992); Al-Amri (1994, 1995a; Ambraseys et al (1994); Al-Amri et al (1998); Alsinawi and Alaydarus (1999); Badawy (2005); Korrat et al (2006); Marzouk (2008); Abdel-Rahman et al (2009);El-Isa (2013a).…”
Section: Historical Seismicity Datamentioning
confidence: 99%
“…Historical and instrumental seismicity of the Sinai Peninsula have been investigated by many researchers [22][23][24][25][26][27]. Twenty-five seismic events have been reported between 95 BC and 1910 AD at various localities with different intensities [28]. The reported intensities were based on recorded damage, which indicates heterogeneous behavior in space or time (Figure 3).…”
Section: Study Areamentioning
confidence: 99%